The use of bisphosphonates for the treatment and prevention of osteoporosis - O. A. Nikitinskaya; N. V. Toroptsova (Современная ревматология)
Osteoporosis (OP) occupies one of the leading places in the structure of morbidity in people over 50 years of age, and its social significance is associated with the main complications – low-energy fractures of the vertebral bodies and bones of the peripheral skeleton, which lead to an increase in disability and mortality among the elderly, being a serious problem for public health. One of the doctor’s goals is the timely administration of anti-osteoporotic treatment. Bisphosphonates (BP) are first-line drugs for the treatment of OP. Since 1995, nitrogen-containing BPs have been widely used, they demonstrate their effect primarily by inhibiting the activity of osteoclasts and stimulating their apoptosis. The efficacy and safety of this class of drugs have been confirmed by numerous studies and many years of clinical practice. Since 2005, the production of generics of alendronic acid began, and later, after the patent protection of other BFs was closed, generics of risedronic, ibandronic and zoledronic acids appeared. In 2019, two domestic generics were registered – ibandronic acid 3 mg for intravenous (IV) injection once every 3 months (Rezoviva) and zoledronic acid 5 mg in 100 ml solution for IV injection once a year (Osteostatics). Since 2020 they have been introduced into clinical practice as part of import substitution, which increased the availability of these drugs and reduced the health care costs.